(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The Abbasid caliphs established a great state that was distinguished by justice, knowledge, literature, and administrative and political progress. This state would not have reached this high level of power and distinction had it not been for a group of successive caliphs who ruled it and were imbued with the morals of Islam. Islam implanted in its children morals that adhered to would lead to stability. The state and society as a whole. One of the defining features of Islamic civilization is its commitment to Islamic ethics, which in turn ensures that everyone is treated equally and without any bias or manipulation of values in the name of relativism or evolution. Justice, honesty, loyalty, and chastity are basic moral principles in Islam. The Messenger, may God bless him and grant him peace, described himself as saying that his mission was to complement and embody these virtuous qualities. A key feature of civilization is that it is based on Islamic morality, which includes enjoining good and forbidding evil, religious tolerance for the people of the Dhimahi, and an emphasis on forgiveness and mercy. All of these aspects of Islamic civilization are unique and were fundamental to its development.